1995
DOI: 10.1074/jbc.270.7.3353
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Pathways Mediate the Opposing Actions of Tumor Necrosis Factor-α and Transforming Growth Factor-β on α2(I) Collagen Gene Transcription

Abstract: Transforming growth factor-beta (TGF-beta) and tumor necrosis factor-alpha (TNF-alpha) are multifunctional peptides intimately involved in the process of extracellular matrix remodeling. We recently showed that TGF-beta stimulates the human alpha 2(I) collagen gene by increasing the affinity of an Sp1-containing transcriptional complex bound to an upstream sequence termed the TbRE (Inagaki, Y., Truter, S. and Ramirez, F. (1994) J. Biol. Chem. 269, 14828-14834). Here, we report that the TbRE-bound complex also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
1
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 28 publications
2
97
1
1
Order By: Relevance
“…The reason for the discrepancy between these two studies is presently not clear. Furthermore, TNF-␣ has been shown to inhibit ␣2(I) collagen transcription via the same response element that mediates TGF-␤ stimulation (32,33). The response elements mediating modulation of ␣2(I) collagen promoter activity by other cytokines have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the discrepancy between these two studies is presently not clear. Furthermore, TNF-␣ has been shown to inhibit ␣2(I) collagen transcription via the same response element that mediates TGF-␤ stimulation (32,33). The response elements mediating modulation of ␣2(I) collagen promoter activity by other cytokines have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…For the gel mobility shift assays, a probe was generated by digestion with BglII and BstXI (Ϫ378 to Ϫ183 bp) of the Ϫ378COL1A2-CAT plasmid, which contains the TGF␤-responsive element (11,12,31,32). This probe was end labeled with [␥-32 P]ATP and T4 kinase (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…Addition of 30 M AdoMet for 24 h after transfection decreased the basal activity of both the Ϫ3500COL1A2-CAT and the Ϫ378COL1A2-CAT reporter vectors. It is interesting that AdoMet lowered CAT activity in cells transfected with the Ϫ378COL1A2-CAT construct, which contains the Ϫ378 to ϩ58 bp region that is essential for increased basal COL1A2 expression and responsiveness to oxidative stress and cytokines such as TNF␣ and TGF␤ (11,12,21,29,32,37).…”
Section: Induction Of Liver Fibrosis In Mouse Col1a2 Promoter Transgementioning
confidence: 99%
See 1 more Smart Citation
“…Speci®cally, we previously demonstrated that TGF-b has an additive, if not synergistic, e ect with pro-in¯ammatory cytokines, such as IL-1 or TNF-a, on type VII collagen gene expression, as measured at both protein and mRNA levels (Mauviel et al, 1994). In contrast, the e ects of TGF-b and TNF-a on type I collagen gene expression are antagonistic, TGF-b being a powerful activator of type I collagen gene promoters (both COL1A1 and COL1A2) while TNF-a exerts an inhibitory e ect (Varga et al, 1987;Inagaki et al, 1995;Chung et al, 1996).…”
Section: Introductionmentioning
confidence: 99%